Study of water Quality in the Savitri River (International Journal of Food and Nutritional Sciences, 2022)
Surface water is used for domestic, industrial, water supply and irrigation all over the world.Nature has given us plenty of water and even then we are feeling the shortage of water for drinking,washing, irrigation and industrial purposes because we have misused and decreased quality of our waterresources to a great extent, which may cause harmful effects on human and aquatic life.